Aktivitas Pelayaran dalam Pelayaran pada Kapal Layar Motor Surya Indah di Desa Pasir Putih Kecamatan Kapala Madan Kabupaten Buru Selatan Provinsi Maluku - Syamsumarlin .; Hasrin Monde Ofu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
This study aims to explain and describe the pattern of patron-client relationship between the owner of the ship, juragang and Ship's Men (ABK) and a revenue sharing system in the cruise Sailing Motor Surya Indah. Data collected by participant observation techniques and in-depth interviews. The data obtained were analyzed by descriptive qualitative. The data analysis is intended to simplify the data obtained so that the younger read and understood. The results showed that shipping activities from the planning stage such as borrowing a boat, determine the rights and obligations of borrowers in the shipping owners and sanctions provided if a violation is found. Furthermore, shipping activities continued with mustard and seek election to take charge of the commodity as well as in shipping. Once all the preparation is complete, then the process of shipping can be done. In the process of shipping, sailors looking for buyers of merchandise and returning home to the island of Labour. Profit-sharing system for the gob done by divided evenly. Before the results is done, all the expenditure during cruise and rental boats separated beforehand. After all expenditures in the calculations, then the net income earned. This net income divided by as many as six people according to the number of whole gob. Keywords: shipping activities